THE ROLE OF HISTORICAL-ARTISTIC LITERATURE IN THE DEVELOPMENT OF SOCIAL MEMORY (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article discusses the role and importance of cultural heritage, historical monuments, historical literature in the development of the national social memory of young people and its strengthening. At the same time, the cultural heritage of the past is associated not only with research from a scientific point of view, but also with the great spiritual heritage created by the ancestors, a monument that brings social and economic capital, and a number of factors related to the formation of a person into a comprehensive personality are analyzed from the point of view scientific objectivity.
Keywords: monument, heritage, historical thinking, Homer, social memory, ancestor, value, education, education, social memory.